2018
DOI: 10.3390/safety4030040
|View full text |Cite|
|
Sign up to set email alerts
|

Driving among Adolescents with Autism Spectrum Disorder and Attention-Deficit Hyperactivity Disorder

Abstract: Over the past several decades there has been a surge of research on the contextual, biological, and psychological factors associated with transportation safety in adolescence. However, we know much less about the factors contributing to transportation safety among adolescents who do not follow a typical developmental trajectory. Adolescents with developmental disabilities (DD) such as Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD) have a wide range of behavioral and psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 94 publications
(145 reference statements)
1
15
0
Order By: Relevance
“…4 In addition, autistic individuals report comorbid anxiety and fear to drive as a common reason for not driving. 13 Overall, *40%-60% of autistic individuals experience anxiety or have an anxiety-related disorder. 14,15 Such anxiety often manifests behind the wheel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 In addition, autistic individuals report comorbid anxiety and fear to drive as a common reason for not driving. 13 Overall, *40%-60% of autistic individuals experience anxiety or have an anxiety-related disorder. 14,15 Such anxiety often manifests behind the wheel.…”
mentioning
confidence: 99%
“…14,15 Such anxiety often manifests behind the wheel. 13 For example, one study found that autistic individuals reported high driving anxiety and commonly requested a companion in the car while driving even after obtaining a driver's license. 16 Additionally, autistic drivers reported not driving for vocational or social purposes.…”
mentioning
confidence: 99%
“…Studies on medical imaging data have gained great popularity with the rapid development of various neuro-imaging technologies. Existing imaging technologies include magnetic resonance imaging (MRI), functional MRI (fMRI), electroencephalography (EEG), diffusion tensor imaging and positron emission tomography (PET) [ 1 , 2 ]. Large amounts of data from different imaging technologies urgently need to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive ability (i.e. executive function, processing speed, verbal learning and memory, and attention) is essential for functioning in daily life, and is involved in making intricate decisions (Bishop et al, 2018). Cognitive decline comprises reduced concentration and attention, poor learning, and memory impairment that negatively affects the quality of life of individuals and their families (Richards and Deary, 2005; Batty et al, 2007).…”
Section: Introductionmentioning
confidence: 99%